ApoE4 Delays Dendritic Spine Formation during Neuron Development and Accelerates Loss of Mature Spines - Evelyn Nwabuisi-Heath; G. William Rebeck; Mary Jo LaDu; Chunjiang Yu (ASN Neuro, 2013)
The ε4 allele of the gene that encodes apolipoprotein E (APOE4) is the greatest genetic risk factor for Alzheimer's disease (AD), while APOE2 reduces AD risk, compared to APOE3. The mechanism(s) underlying the effects of APOE on AD pathology remains unclear. In vivo , dendritic spine density is lower in APOE4-targeted replacement (APOE-TR) mice compared with APOE2- and APOE3-TR mice. To investigate whether this apoE4-induced decrease in spine density results from alterations in the formation or the loss of dendritic spines, the effects of neuron age and apoE isoform on the total number and subclasses of spines were examined in long-term wild-type neurons co-cultured with glia from APOE2-, APOE3- and APOE4-TR mice. Dendritic spine density and maturation were evaluated by immunocytochemistry via the presence of drebrin (an actin-binding protein) with GluN1 (NMDA receptor subunit) and GluA2 (AMPA receptor subunit) clusters. ApoE isoform effects were analyzed via a method previously established that identifies phases of spine formation (day-in-vitro, DIV10–18), maintenance (DIV18–21) and loss (DIV21–26). In the formation phase, apoE4 delayed total spine formation. During the maintenance phase, the density of GluN1 + GluA2 spines did not change with apoE2, while the density of these spines decreased with apoE4 compared to apoE3, primarily due to the loss of GluA2 in spines. During the loss phase, total spine density was lower in neurons with apoE4 compared to apoE3. Thus, apoE4 delays total spine formation and may induce early synaptic dysfunction via impaired regulation of GluA2 in spines.